Odpowiedź :
Odpowiedź:
a) x1=1; x2=3
b) W(2,-3)
zaraz dodam zalacznik z obliczeniami:)
Odpowiedź:
[tex]f(x)=3x^2-12x+9\\\\\\a)\\\\3x^2-12x+9=0\\\\a=3\ \ ,\ \ b=-12\ \ ,\ \ c=9\\\\\Delta=b^2-4ac\\\\\Delta=(-12)^2-4\cdot3\cdot9=144-108=36\\\\\sqrt{\Delta}=\sqrt{36}=6\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-6}{2\cdot3}=\frac{12-6}{6}=\frac{6}{6}=1\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+6}{2\cdot3}=\frac{12+6}{6}=\frac{18}{6}=3[/tex]
[tex]b)\\\\p=\frac{-b}{2a}=\frac{-(-12)}{2\cdot3}=\frac{12}{6}=2\\\\q=\frac{-\Delta}{4a}=\frac{-36}{4\cdot3}=\frac{-36}{12}=-3[/tex]